Sistem Monitoring Pemberian Pakan Ikan Di Aquarium Ikan Hias Menggunakan Aplikasi Blynk Dengan Memanfaatkan Teknologi Iot - Siti Ma’shumah; Ellys Kumala Pramarthaningthyas; Fathur Rohman (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
Technological advances in the industrial era 4.0 mean that various things must prioritize convenience and efficiency in carrying out daily work such as carrying out automatic maintenance and control in the home. This has made many people able to produce various forms of technology that can be controlled automatically and help with work. people who can't take up much time. OT is a technology built to provide ease of work that can be connected to each other using the internet. One use of IoT technology is in the household sector to feed ornamental fish according to need and monitor remaining feed. This tool is designed for NodeMCU as control and an internet connection that is integrated with the Blink application. This tool consists of an HC-SR04 sensor input and a DS3231 RTC timer. The output of this tool uses a servo motor to open and close the contents of the fish feed. Arduino IDE software is used in NodeMCU coding and the Blynk application is used to connect the smartphone and NodeMCU. Based on the results of testing carried out, the system success rate has an average of 95% success. Meanwhile, the average delay is 0.052367 milliseconds.